2007
DOI: 10.4049/jimmunol.178.11.7450
|View full text |Cite
|
Sign up to set email alerts
|

A Virus-Like Particle-Based Vaccine Selectively Targeting Soluble TNF-α Protects from Arthritis without Inducing Reactivation of Latent Tuberculosis

Abstract: Neutralization of the proinflammatory cytokine TNF-α by mAbs or soluble receptors represents an effective treatment for chronic inflammatory disorders such as rheumatoid arthritis, psoriasis, or Crohn’s disease. In this study, we describe a novel active immunization approach against TNF-α, which results in the induction of high titers of therapeutically active autoantibodies. Immunization of mice with virus-like particles of the bacteriophage Qβ covalently linked to either the entire soluble TNF-α protein (Qβ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 38 publications
(35 reference statements)
3
74
0
1
Order By: Relevance
“…In addition, anti-TNF-␣ antibodies (17,18) and soluble chimeric TNF-␣ receptors (19,20) are widely used in the treatment of autoimmune disease, and a number of approaches are being pursued to develop TNF-␣-specific vaccines for clinical use. The latter include recombinant TNF-␣ molecules containing foreign immunodominant T-helper epitopes, TNF-␣ fusions to virus-like particles of the bacteriophage Q ␤ , and keyhole limpet hemocyanin-TNF-␣ heterocomplexes (4,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, anti-TNF-␣ antibodies (17,18) and soluble chimeric TNF-␣ receptors (19,20) are widely used in the treatment of autoimmune disease, and a number of approaches are being pursued to develop TNF-␣-specific vaccines for clinical use. The latter include recombinant TNF-␣ molecules containing foreign immunodominant T-helper epitopes, TNF-␣ fusions to virus-like particles of the bacteriophage Q ␤ , and keyhole limpet hemocyanin-TNF-␣ heterocomplexes (4,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Virus-like particles induce potent B-cell responses even in the absence of adjuvants (30,31), and as carrier proteins, they are preferable to other proteins. More recently, cytokine peptide-based virus-like particle vaccines are being investigated by chemically conjugating synthesized cytokine peptides to bacteriophage Qβ virus-like particles (33). Compared with the vaccines that are currently being investigated, the p40 vaccine used in the present study has unique advantages: (1) it uses a small peptide, avoiding possible cross-reaction with other self proteins; (2) it is highly antigenic, eliciting longlasting specific antibodies without the use of an adjuvant owing to its virus-like particle feature; (3) it is a recombinant protein, making it easier to prepare and to control the quality of the vaccine than those by chemical coupling (33); (4) the safety of the vaccine carrier HBcAg has been confirmed in a phase I clinical trial for a malaria vaccine used in humans (34), making this vaccine even more attractive for human use.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach to vaccine design, we have previously demonstrated that levels of neutralizing Ab responses against self-proteins can be induced that are high enough to show therapeutic effectiveness in mice (31)(32)(33)(34)(35). We have also demonstrated that efficacy established in animal models can be translated into efficacy in humans (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…To test the feasibility of this concept, we generated a vaccine comprising mature NGF covalently conjugated to a virus-like particle (VLP) carrier derived from the bacteriophage Qb. We have previously validated this approach both preclinically and clinically for other Ags (30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%